The Effectiveness of Biofilter to Reduce Fatty Oil and Ammonia Content in the Butchery Liquid Waste - Sormin, Dessy Novelia; Harahap, Sampe; Purwanto, Eko (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract The butchery liquid waste is rich in fatty oil and ammonia and its need to be processed before being dispose to environment. A study aims to reduce the fatty oil and ammonia content in that waste has been conducted in March – April 2018. The waste (315 L) was treated using a batch system that was consisted of 2 aerob and 2 anaerob tanks. The butchery liquid waste was kept for 10 days in anaerob tanks, 7 days in aerob tanks. By the end of the experiment, the fatty oil reduced from 63 mg/l to 4.5 mg/l (the effectiveness was of 92.85 %). While the ammonia reduced from 30 mg/l – 0.8 mg/l (the effectiveness was 97.33 %). Other water quality parameters such as DO was improved (from 1 mg/L to 5 mg/L), and pH also increased (from 6 to 8). The treated waste is used as media for rearing Brachionus plicatilis.Observations of Brachionus plicatilis were performed for 8 days. The peak of rotifera growth occurs in the sixth day, reaching 950,000 cells/ml. Based on data obtained, it can be concluded that the combination of bio filters is effective to reduce the fatty oil and ammonia content in the butchery liquid waste. Keyword :thebutchery liquid waste, organic pollutants, batch system, Brachionus plicatilis